2012
DOI: 10.4081/reumatismo.2012.299
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of influenza-like illness into a cohort of patients affected by chronic inflammatory rheumatism and treated with biological agents

Abstract: This study aimed to evaluate the incidence of influenza-like illness (ILI), from October 2009 to May 2010, in a group of patients suffering from chronic inflammatory rheumatism and treated with biological therapies. At the end of 2009-2010 influenza season, 159 patients under biological therapies answered to a questionnaire distributed 8 months before and were deeply interviewed. The group included 69 men and 90 women (mean age 47.6); forty-nine suffering from rheumatoid arthritis, 61 with psoriatic arthritis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 17 publications
0
12
1
Order By: Relevance
“…Data focused on viral respiratory infections in bDMARD cohort are still very limited. The incidence of influenza-like infections observed in a cohort of 159 Italian patients treated with bDMARDs during the influenza season 2009-2010 was higher than the value reported in a wide sample of Italian population in the same period, even though no important complications or hospitalizations have been reported [62]. Overall, post-marketing experience is relatively reassuring that anti-TNF treated patients may not be at any specifically increased risk of influenza and that severe adverse outcomes, including death, do not appear to be exceedingly frequent [63].…”
Section: Bdmardscontrasting
confidence: 60%
“…Data focused on viral respiratory infections in bDMARD cohort are still very limited. The incidence of influenza-like infections observed in a cohort of 159 Italian patients treated with bDMARDs during the influenza season 2009-2010 was higher than the value reported in a wide sample of Italian population in the same period, even though no important complications or hospitalizations have been reported [62]. Overall, post-marketing experience is relatively reassuring that anti-TNF treated patients may not be at any specifically increased risk of influenza and that severe adverse outcomes, including death, do not appear to be exceedingly frequent [63].…”
Section: Bdmardscontrasting
confidence: 60%
“…The use anti-tumour necrosis factor (anti-TNF) therapy was associated with a higher risk of contracting influenza in this study. A questionnaire-based study from Italy reported a 17% incidence of ILI among patients with RA, psoriatic arthritis (PsA), ankylosing spondylitis (AS) and spondyloarthropathy (SpA) treated with biological treatments,12 compared with a lower incidence of influenza in the general Italian population (9.7%). Notably, no significant influenza-related morbidity or hospitalisations were reported in this study.…”
Section: Resultsmentioning
confidence: 99%
“…2 Other RD (particularly psoriatic arthritis, ankylosing spondylitis, and spondyloarthropathy) treated with biologic disease-modifying anti-rheumatic drugs (DMARD) have been associated with a higher incidence of influenza-like illness compared with the general population. 6 In a cohort of ANCA-associated vasculitis, the combined incidence of influenza and pneumonia was higher compared to the general population. 7 Vaccines are one of the safest and most effective public health interventions.…”
Section: Introductionmentioning
confidence: 95%